2003
DOI: 10.1152/ajpregu.00700.2002
|View full text |Cite
|
Sign up to set email alerts
|

ANG II is involved in the LPS-induced production of proinflammatory cytokines in dehydrated rats

Abstract: Miyoshi, Michio, Katsumi Nagata, Toshiaki Imoto, Osamu Goto, Akiko Ishida, and Tatsuo Watanabe. ANG II is involved in the LPS-induced production of proinflammatory cytokines in dehydrated rats. Am J Physiol Regul Integr Comp Physiol 284: R1092-R1097, 2003 10.1152/ajpregu.00700.2002We have previously reported results that led us to speculate that ANG II is involved in the LPSinduced production of proinflammatory cytokines, especially under dehydrated conditions. To test this possibility, in this study we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
26
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 28 publications
5
26
1
Order By: Relevance
“…These data clearly demonstrate that AT 1 signaling is required for DC full response to LPS. This conclusion is further supported by the observation of other groups using AT 1 antagonists or angiotensin-converting enzyme inhibitors, who postulated that AII enhances the LPS-induced production of cytokines in different cell types (Fukuzawa et al, 1997;Constantinescu et al, 1998;Miyoshi et al, 2003Miyoshi et al, , 2008Shimizu et al, 2004).…”
Section: Discussionsupporting
confidence: 60%
“…These data clearly demonstrate that AT 1 signaling is required for DC full response to LPS. This conclusion is further supported by the observation of other groups using AT 1 antagonists or angiotensin-converting enzyme inhibitors, who postulated that AII enhances the LPS-induced production of cytokines in different cell types (Fukuzawa et al, 1997;Constantinescu et al, 1998;Miyoshi et al, 2003Miyoshi et al, , 2008Shimizu et al, 2004).…”
Section: Discussionsupporting
confidence: 60%
“…In other words, NP and ANG II participate in blood pressure and body fluid regulation through physiological mechanisms that act counter to each other. Recently, we found that ANG II and its type 1 receptor are involved in the bacterial endotoxin (lipopolysaccharide; LPS)-induced fever and production of pyrogenic cytokines such as interleukin (IL)-1 (a step involved in fever induction) (Watanabe et al, 2000;Miyoshi et al, 2003). This finding is in good agreement with the fact that ANG II plays an important role in the induction of inflammatory responses (Suzuki et al, 2003).…”
supporting
confidence: 70%
“…injection of LPS increases the liver concentration of IL-1␤ in dehydrated rats, and this effect can be significantly attenuated by an ACE inhibitor or by an AT 1 receptor antagonist, in each case given i.v. (Miyoshi et al, 2003). However, we found that an i.v.…”
mentioning
confidence: 59%